Stakeholder theory and shareholder theory application in construction field: systematic scoping review - Eunice Achina Agyemang; Innocent Musonda; Sam Zulu (Construction Economics and Building)
Stakeholder theory and shareholder theory are essential frameworks for understanding construction projects, influencing sustainability, project success, and decision-making. Although some studies have explored these theories, there is a notable gap in retrospectively analyzing their application within the construction context. Therefore, this study seeks to systematically review stakeholder and shareholder theories to determine which theoretical approach is predominantly used in construction studies, assess the thematic areas where stakeholder theory or shareholder theory is applied in construction studies, and identify future research and gaps in the application of these theories in construction studies. The study adopted Arkesy and O'Malley's five-stage framework to conduct a systematic scoping review of 1726 articles from Scopus and Google Scholar databases, focusing on stakeholder theory or shareholder theory. The selection process followed the PRISMA framework, with 31 articles meeting the inclusion criteria. The data was analyzed using content analysis. The study showed an increased focus on stakeholder theory as compared to shareholder theory. There were 10 themes identified under stakeholder theory with ‘stakeholder management’ being the predominant theme. Shareholder theory, on the other hand, had only 2 themes, with ‘shareholder value creation’ being the predominant theme. The few themes identified under shareholder theory were as a result of the scarcity of research in this area. This calls for more research in the application of shareholder theory. Remarkably, there is a notable lack of research that integrates these two theories. This highlights the opportunity for the integration of these theories to address complex challenges in the construction industry.